Association between inflammatory-response gene polymorphisms and risk of acute kidney injury in children. Issue 6 (14th December 2018) - He, Jing; Xie, Guoyan; Wu, Hui; Xu, Song; Xie, Jun; Chen, Youyuan; Zhao, Xinqian
Abstract : In the present study, we investigated the association of 12 polymorphisms in six inflammatory-response genes ( TNF, IL6, IL10, IL18, NFKB1 and NFKBIA ) with risk of acute kidney injury (AKI) in children. The polymorphisms were genotyped in 1138 children with AKI and 1382 non-AKI controls. Logistic regression analysis was performed to calculate the odds ratio for estimating the risk association. After accounting for Bonferroni correction and adjustment for potential confounders, significant association was observed for NFKB1 rs28362491, NFKBIA rs2233406 and NFKBIA rs696 polymorphisms ( P < 0.004). All three polymorphisms were associated with a reduced risk of AKI. For rs28362491 polymorphism, the OR for ID vs. II comparison was 0.75 (95% CI = 0.58–0.83) while that for DD vs. II was 0.44 (95% CI = 0.30–0.67). For rs2233406 polymorphism, the CT vs. CC comparison showed an OR of 0.90 (95% CI = 0.39–0.99), while the TT vs. CC comparison showed an OR of 0.43 (95% CI = 0.33–0.80). For rs696 polymorphism, the OR for AG vs. AA comparison was 0.71 (95% CI = 0.43–0.89), while the GG vs. AA comparison showed an OR of 0.39 (95% CI = 0.21–0.71). In conclusion, NFKB1 rs28362491, NFKBIA rs2233406 and NFKBIA rs696 polymorphisms may serve as biomarkers for predicting risk of AKI in children.